STABILISASI TANAH TAMBAK DENGAN VARIASI CAMPURAN SEMEN ANDALAS SEBAGAI LAPISAN SUBGRADE - Faisal Abdullah (Portal: Jurnal Teknik Sipil, 2011)
This paper discusses the results of the study, conducted to determine the effect of variations in cement content of the waiting time of curing (curing time) after the mixing process with a ground. Soils studied were from Jalan Simpang Loskala Pertamina Lhokseumawe. Portland cement used is the type of Andalas, with mixtures of two kinds of variation is 3% and 5%, a waiting period of 1 day, 3 day and 7 days. Physical properties of the test results, according to AASHTO; land into group A, 2-6, while according to the USCS; the land is included in group SC (sandy clay), visual observation as well, so the soil is sandy silt soil type, so it is non-cohesive and did not have a value of plasticity. Based on laboratory testing showed that the addition of the percentage of cement can increase the bearing capacity of the soil as well as the duration of curing.Keywords: cement content, bearing capacity, duration of curing